MEDICAL MYCOLOGY, PSYCHIATRY, HEPATOLOGY — ACTUAL INTERDISCIPLINARY CLINICAL PROBLEM, SOLUTION DEVELOPMENT, TREATMENT PECULIARITIES - E. V. Gerasimchuk; V. V. Gladko; M. Y. Gerasimchuk (Архивъ внутренней медицины)
Close clinical and phylogenetic relationship of skin conditions, mental health and disorders of the hepatobiliary system was established. The aim of the study was to evaluate the efficacy of systemic antifungal monotherapy (terbinafine) plus S-adenosylmethionine (AdoMet, SAMe), as compared to terbinafine alone, in patients (n=108) with onychomycosis and different chronic itching dermatoses. Management with terbinafine plus hepatoprotective agent was associated with better therapy response, SAMe supplementation seem to be effective in the prevention of liver injury, normalization of biochemical parameters and neuropsychological evaluation of patients.